Strong Behavioral Effects of Omnivorous Fish on Amphibian Oviposition Habitat Selection: Potential Consequences for Ecosystem Shifts - Kloskowski, Janusz; Nieoczym, Marek (Frontiers in Ecology and Evolution, 2022)
Perceived predation risk to offspring may have similar ultimate community-level impacts to those of consumptive trophic interactions. The present study investigated the behavioral effects of common carp Cyprinus carpio – an omnivorous fish capable of triggering an ecosystem shift to an algae-dominated state – on anurans, using a natural experiment conducted in a system of fish-stocked ponds. We compared oviposition patterns and larval densities of anurans and abundance of zooplankton and phytoplankton in ponds where fish were virtually absent and ponds where common carp was dominant. All studied anuran species bred in fish-poor ponds, while in ponds with high fish densities most of them oviposited infrequently or virtually did not breed. Oviposition habitat selection coupled with fish trophic pressure resulted in diametrically different tadpole densities between fish-poor and fish-dominated ponds. The alimentary tract contents of tadpoles of three locally common anurans, Pelobates fuscus, Hyla orientalis and Rana temporaria, contained large numbers of unicellular algae, but also significant numbers of zooplanktonic grazers. According to stable nitrogen isotope analyses, tadpoles occupied a trophic level similar to a primary consumer, snail Lymnaea stagnalis, indicating that they fed mainly on algae. While total biomass of crustacean zooplankton did not differ between pond types, chlorophyll a concentrations were low in fish-poor ponds compared to fish-dominated ponds and negatively related to total tadpole biomass. Our findings indicate that scarcity of anuran larvae, resulting mainly from the behavioral responses of breeding anurans to fish predation risk, may facilitate algal production, although ecosystem shifts in the presence of fish occur along more pathways than a top-down cascade.